Le théâtre historique pour la jeunesse sous la Restauration et la monarchie de Juillet : propagande royale ou éducation politique ? - Calderone Amélie (Amnis)
The beginning of the 19th century is marked by the exponential development of dramatic literature and an increased interest in historical themes. Children and young people are a target audience as evidenced by the spate of so-called “historical” plays, disseminated in printed form or performed on stage. What was the purpose of these dramatized historical fiction? Were they supposed to teach History, thus supporting a discipline that was progressively taking centre stage in education? How did they (re)write great collective events and assess past acts of violence? Was the historical event important in itself or was it but the vehicle of a broader plan to entertain, indoctrinate, raise moral standards and shape young minds? The study of a body of 8 plays dating back to the French Restoration and the July Monarchy provides some insight into possible answers. Apparently, the point is not so much to ‘write’ History as to develop a common middle-class culture and generate a sense of French identity through references to famous figures. The ideological ambition is also quite obvious: while instilling the love of royalty in young audiences at the beginning of the Restoration, the plays should also provide moral role models designed to ensure long-lasting political stability. Interestingly, at the end of the reign of King Charles X, dramatic literature takes a more critical turn and begins to spread more liberal and republican values with a view to educating future citizens whose voting decisions will bear upon the political destiny of their country.